P07 Evidence-based guidance to inform consent seeking in children's critical care trials. (27th April 2015) - Woolfall, K; Frith, L; Young, B
Abstract : Aims: Challenges in seeking parents' consent for research at the point when their child is critically ill have been a significant barrier to improving treatments for children and conducting trials. In 2008 UK legislation was amended to enable consent for emergency research to be sought after a child has been given the investigational drug or device. This is known as deferred consent. CONNECT is the first UK study to explore parent and practitioner views and experiences of deferred consent in children's clinical care trials. It aimed to integrate evidence and ethical theory to inform practice guidelines to optimise recruitment and consent in this challenging setting. Methods: Mixed methods qualitative and quantitative study with 354 participants (292 parents, 39 nurses, 19 doctors and 4 Clinical Trials Unit practitioners). We integrated findings with previous research and ethical theory to develop draft guidance on deferred consent. The CONNECT advisory group and 32 key stakeholders (critical care practitioners, ethicists and parents) contributed to the development of the final CONNECT guidance. Results: Parents may be initially shocked or angered to discover their child can be entered into a trial without their prior consent. However practitioner explanations of why consent is deferred can help address parents' initial concerns and reassure them. Parents view deferred consent as more acceptable for trials of medical interventions already used in clinical practice than trials involving new interventions or a change in clinical practice. Practitioners experienced in deferred consent describe how families are receptive to the consent method, if conducted sensitively and if the timing is appropriate. CONNECT guidance provides recommendations to inform: 1) pre-trial research for potentially challenging trials; 2) publicising trials that use deferred consent; 3) seeking deferred consent; 4) seeking deferred consent when a child has died; 5) written trial information; and 6) child assent. Conclusion: Those involved in the funding, design, conduct and ethical review of critical care trials can use CONNECT guidance to help ensure approaches to deferred consent are appropriate to the needs of children and their parents. Further research is required to explore the views of children and bereaved parents who have experienced deferred consent.